2021
DOI: 10.1021/acsaem.0c02502
|View full text |Cite
|
Sign up to set email alerts
|

Heterostructured Ni/NiO Nanoparticles on 1D Porous MoOx for Hydrolysis of Ammonia Borane

Abstract: The hydrolysis of AB has been regarded as a kind of secure and efficient method for hydrogen generation. However, the development of economical and stable catalysts with high catalytic activities remains a bottleneck for realizing further industrial application of AB. Herein, high-loading heterostructured Ni/NiO nanoparticles with different Ni/NiO weight ratios anchored on one-dimensional porous MoO x nanorods (denoted as Ni/NiO@MoO x ) have been synthesized and introduced into the hydrolysis of AB for the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 65 publications
4
12
0
Order By: Relevance
“…Figure a shows the high-resolution XPS of Ni 2p, which could be divided into the typical components of Ni 0 , oxidized Ni species, and Ni satellite. As shown in Figure a, for freshly prepared catalysts, the observed XPS peaks are located at 853.0–853.6 eV corresponding to the Ni 0 , ,, and this peak is 0.3–0.9 eV higher than the standard metallic Ni; this result is consistent with the reported literature . This blue shift of the Ni XPS peak in the 10Ni/CNTs is possibly related to the electron transfer from Ni to CNTs support, indicating the modulation of the electronic structure of Ni by CNTs, which is evidence of the strong metal–support interaction between Ni and CNTs substrate.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Figure a shows the high-resolution XPS of Ni 2p, which could be divided into the typical components of Ni 0 , oxidized Ni species, and Ni satellite. As shown in Figure a, for freshly prepared catalysts, the observed XPS peaks are located at 853.0–853.6 eV corresponding to the Ni 0 , ,, and this peak is 0.3–0.9 eV higher than the standard metallic Ni; this result is consistent with the reported literature . This blue shift of the Ni XPS peak in the 10Ni/CNTs is possibly related to the electron transfer from Ni to CNTs support, indicating the modulation of the electronic structure of Ni by CNTs, which is evidence of the strong metal–support interaction between Ni and CNTs substrate.…”
Section: Resultssupporting
confidence: 89%
“…As shown in Figure b, for 10Ni30Mo 2 C/CNTs, the peak observed at 228.6 eV is assigned to the presence of Mo 2+ species in the β-Mo 2 C form. The other bands at BE values of 229.5 and 233.0 eV are attributed to the oxidation states of Mo 4+ and Mo 6+ , which, respectively, are derived from the MoO 2 and MoO 3 phases due to the partial surface oxidation of Mo x C when exposed to air . In the case of 10Ni30MoC/CNTs, besides the peak of Mo 4+ species (229.5 eV), other two peaks with Mo 3d 5/2 binding energies of 231.4 and 233.0 eV are assigned to Mo 5+ and Mo 6+ , respectively.…”
Section: Resultsmentioning
confidence: 96%
“…Many studies had tried to use transition-metal NPs to partially or completely replace noble-metal NPs. But it is still necessary to enhance the activity and stability of transition-metal NPs because they tend to be oxidized and aggregate into larger particles. Researchers had proposed a variety of solutions, and the most commonly used method was the loading method. The carriers included G, , C 3 N 4 , , porous metal–organic framework (MOF), silica, , carbons, , PVP, α-MoC, MoO x , TiO 2 , etc. Among transition-metal NPs, because the Cu element is abundant in the earth’s crust and Cu NPs have excellent catalytic properties, Cu and Cu-based NPs have attracted extensive interest. , However, Cu NPs are extremely unstable under environmental conditions and their instability limited their practical applications .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the hydrogen desorption property of NaBH 4 was impacted due to the presence of different ions. He et al 33 reported development of a stable and economical catalysis system for AB hydrolysis. They utilized Ni/NiO nanoparticles and porous MoOx nanorods (denoted as Ni/ NiO@MoOx).…”
Section: ■ Introductionmentioning
confidence: 99%